Pengaruh Earning Per Share (EPS) dan Dividen Per Share (DPS) Terhadap Harga Saham PT Indo Tambangraya Megah Tbk - Arifudin Arifudin; Alwi Alwi; Aris Munandar (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to determine whether there is an influence of Earning Per Share (EPS) and Dividend Per Share (DPS) on the share price of PT Indo Tambangraya Megah Tbk. The research method used is associative research with a quantitative approach. The population used in this research is all of PT's financial reports. Indo Tambang Raya Mega Tbk. Since being listed on the IDX from 2007 to 2023, which is 17 years. The sample used in this research uses financial report data from PT. Indo Tambang Raya Mega Tbk. in the form of reports of net income, dividends and share prices, for 12 years from 2010 to 2021, the technique used in this research is purposive sampling technique. The results of this research show that (1) Earning Per Share (EPS) does not have a partially significant effect on share prices at PT. Indo Tambangraya Megah Tbk. (2) Dividend Per Share (DPS) has a partially significant effect on share prices at PT. Indo Tambangraya Megah Tbk. (3) Earning Per Share (EPS) and Dividend Per Share (DPS) simultaneously have a significant effect on share prices at PT. Indo Tambangraya Megah Tbk..